INTERESTS OF UZBEKISTAN IN THE COOPERATION PROCESS IN CENTRAL ASIA - Oybek Ochilovich Sirojov (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The process of cooperation is closely linked with national interests and their satisfaction. First, states enter into a process of cooperation based on national interests. Second, regional cooperation begins with the balance of national interests and develops through harmonization. Third, regional interests, which are the basis of regional cooperation, are formed on the basis of national interests. Therefore, it is important to study and analyze the interests of each entity involved in the collaboration process. Based on the above, in this article we will focus on the interests of Uzbekistan in the process of regional cooperation and their reflection.